PENGARUH TEKNIK RELEASING TERHADAP KECEMASAN PADA LANSIA - Setyowati, Sri; Sigit Purnomo, Parmadi; Agustina Rahayu, Bety; Yulina Amry, Riza (Coping: Community of Publishing in Nursing; Vol 10 No 5 (2022): Oktober 2022DO - 10.24843/coping.2022.v10.i05.p13, 2022)
The elderly population in Indonesia will continue to increase rapidly in 2021. The emergence of problems in the elderly is often interpreted as a period of decline, because this period is considered the final phase of life. Anxiety is still a problem that must be experienced by the elderly. There are many ways to overcome anxiety, one of which is the releasing technique. The purpose of this study was to determine the effect of releasing techniques on anxiety in the elderly. The type of research used is pre-experimental with one group pre-test post-test design. The population in this study were all elderly members of the Melati Elderly Posyandu, Karet Hamlet, Pleret District, Bantul Regency, Yogyakarta, as many as 19 elderly people. The sampling technique used was total sampling. This research was conducted in September 2021. The instrument used to measure anxiety is the Zung Self Rating Anxiety Scale (ZSAS/ZSRAS) questionnaire. While the intervention given to overcome anxiety is a releasing technique to release emotions by acknowledging the emotions that are felt at that time, asking for the emotions to be raised at that time, and asking for what to expect at that time. Data analysis used a paired t-test analysis test. The results showed that the majority of respondents before being given the releasing technique showed that the elderly with mild anxiety were 68,4%, while after being given the intervention there was an increase in the number of respondents with mild anxiety by 84,2%. Paired t-test analysis shows the significance value 0,000 (<0,05) indicating that there is an influence between variables. The releasing technique has a positive effect on reducing anxiety in the elderly.